Impacts of dental checkups on oral function among Japanese older adults - Tin Zar Tun; Kaung Myat Thwin; Sachiko Takehara; Kumiko Minagawa; Noboru Kaneko; Hiroshi Ogawa (Scientific Reports)
Abstract Dental checkups are integral to maintaining oral function in older adults and are a critical determinant of overall health and quality of life. However, their impact on oral function parameters remains understudied. This study investigated the association between dental checkup attendance and oral function in older adults. This cross-sectional study recruited a convenience sample of 235 older adults (75.1 ± 5.6 years, 125 males). Participants were categorized based on biannual dental checkup attendance. Seven oral parameters were assessed: oral cleanliness, oral dryness, occlusal support, oral motor function, tongue pressure, masticatory performance, and swallowing function. Statistical analyses included the Mann‒Whitney U test, chi-squared test, and linear regression analysis. Significant differences between attendees and non-attendees were found in sex, body mass index, and oral hygiene practices. Oral cleanliness (p = 0.005), masticatory performance (p < 0.001), and swallowing function (p = 0.001) were significantly better in checkup attendees. Non-attendance at dental checkups was consistently associated with the extent of declined oral function in crude (B:0.45; 95%CI:0.12,0.77) and fully adjusted models (B:0.56; 95%CI:0.16,0.97). Given the positive association between dental checkup non-adherence and declined oral function, encouraging community-based awareness campaigns with accessible dental care could promote checkup attendance. Consequently, it contributes to maintaining oral function in the older adult population.